Enhancing Local Food Industry: Production of “Sehati” Marning Corn in Bantaeng Regency - Lestari, Mega Fia; Syaiful, Syaiful; Irwan , Muhammad; Sitanggang, Boy Chandra; Hermansyah, Hermansyah; Odilia Valentine; Aras, Neny Rasnyanti M; Ratlalan, Roberth Marshall; Abidin, Zainal; Supu, Abd Rachman (Penerbit Goodwood, 2025)
Purpose: The local food processing business is essential to the Indonesian economy. Lumpangan Village in Bantaeng Regency, South Sulawesi, has great potential due to the Small and Medium Enterprises (SME) product